2018
DOI: 10.1155/2018/5462959
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Depression among PLHIV in Ethiopia: Systematic Review and Meta-Analysis, 2017

Abstract: Background Depression is a substantial contributor to the global burden of disease and affects people in all communities across the globe. Depression is the most common psychiatric problem associated with HIV/AIDS and half of all PLWHIV with depression go underdiagnosed and untreated. Psychiatric complications of HIVAIDS delay mental health services in less affluent countries. However, there is lack of study with regard to the pooled estimation prevalence of depression in PLWHIV in Ethiopia. Objectives The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 29 publications
6
49
1
Order By: Relevance
“…In Ethiopia, the threat of HIV treatment failure is becoming a continuing discussion. This might be due to poor HIV care services, delayed to recognize treatment failure, [34], late initiation of HAART [33], high burden of opportunistic infections [35], lack of appropriate nutritional support [36], ART-associated adverse reaction, [37] and frequent psychological problem [38,39]. Besides, the absence of frequent therapeutic drug monitors and/ or resistance testing while the patient is still on the suspect or failing regimen.…”
Section: Discussionmentioning
confidence: 99%
“…In Ethiopia, the threat of HIV treatment failure is becoming a continuing discussion. This might be due to poor HIV care services, delayed to recognize treatment failure, [34], late initiation of HAART [33], high burden of opportunistic infections [35], lack of appropriate nutritional support [36], ART-associated adverse reaction, [37] and frequent psychological problem [38,39]. Besides, the absence of frequent therapeutic drug monitors and/ or resistance testing while the patient is still on the suspect or failing regimen.…”
Section: Discussionmentioning
confidence: 99%
“…In Ethiopia threat of HIV treatment failure is becoming appointed discussion. This might be due to implementation of poor HIV care, delaying on recognition of symptom of treatment failure, (35), late initiation of HAART (36), high burden of opportunistic infections (37), lack of well nutritional support (38), ART associated adverse reaction, (39) and frequent psychological problem (40,41) are recorded in Ethiopia. Besides, absence of frequent therapeutic drug monitors and/ or resistance testing while the patient is still on the suspect or failing regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Univariate analyses were first used to assess the unadjusted odds ratios for each variable. Although there were divergence results about socio‐demographic differences of depression and anxiety in previous studies, most reported a significant association with gender, age, residence, marital status and socioeconomic status (which is usually measured by education, employment and income) in people living with HIV and those who are not . Thus, we adjusted the crude odds ratios for each clinical and psychosocial factor to account for these variables and the residual pseudo‐likelihood technique was used for parameter estimation.…”
Section: Methodsmentioning
confidence: 99%